The MN RIDE pilot: feasibility of a synchronous, remotely delivered, aerobic exercise training program for rural-dwelling adults with subjective cognitive decline - Dereck Salisbury; Wayne Warry; Joshua Fergen; Kirsten Cruikshank; Patricia Soderlund; Kristen Jacklin (James Cook University, 2023)
Introduction: Out of all the modifiable risk factors for Alzheimer's disease and related dementias (ADRD), physical inactivity is the strongest. Rural residents have an increased risk for dementia and face significant barriers to accessing ADRD information, caregiving support, and memory-related services, which contributes to substandard care. Rural communities have greater barriers to participating in physical activity, and in particular exercise, due to lack of social support, travel/weather problems, and lack of facilities/equipment. The purpose of this pilot study was to implement and evaluate the feasibility and safety of a synchronous, remotely delivered, aerobic exercise (AEx) telerehabilitation program in persons with subjective cognitive decline (SCD) living in rural areas. Methods: The Minnesota Rehabilitation Intervention for Dementia Evasion for rural residents (MN RIDE) pilot study was one of five pilot studies conducted through the Center for Community Engaged Rural Dementia and Alzheimer's Research, conducted in collaboration with the Memory Keepers Medical Discovery Team. The Memory Keepers Medical Discovery Team employs a community-based participatory research model and uses a community advisory group, community-based researchers and a rural community engagement specialist to ensure research studies are aligned with rural community needs and to facilitate the recruitment of participants living in rural northern Minnesota. The MN RIDE study employed a single group, pretest-post-test design to test the feasibility and safety of an AEx-focused synchronous telerehabilitation program in rural-living middle-aged or older adults (>45 years) with SCD (indicated by answering yes to both, 'Do you perceive memory or cognitive difficulties?' and 'In the last two years, has your cognition or memory declined?'). All 36 AEx sessions (conducted over 12 weeks) were supervised remotely via smart devices and Zoom. The AEx program was classified as moderate intensity stationary cycling starting at a rating of perceived exertion (RPE) 11-12 or for 30-35 minutes in session 1, and was alternatively increased by 1-point RPE or 5-minute increments as tolerated up to RPE 12-14 for 50 minutes a session over time (by session 18). Secondarily, moderate intensity was defined as achieving an exercise heart rate of 64-76% of age-predicted maximum heart rate (HRmax). Feasibility and safety outcomes were assessed by session attendance, intensity adherence, presence of adverse events, and participant satisfaction. Results: The average age of the study sample (n=9) was 57.44±7.16 years (average age of SCD onset 53.44±7.47 years) with 14.00±5.57 years of education and 88.9% female. All patients completed the study, resulting in a dropout rate of 0%. Out of the possible 324 sessions scheduled, 276 were attended (85% session adherence). Average intensity metrics achieved over the AEx sessions were RPE 13.2±0.5 and HRmax 72.0±7.9%, which both represent of moderate intensity AEx metrics. No adverse events were reported. Conclusion: This pilot study further provides the first evidence of preliminary feasibility of synchronous audiovisual, telerehabilitation programs delivered to rural residents at risk for ADRD. Thus, exercise telerehabilitation programs that focus on AEx could be viable and useful tools to overcome situations with limited access to healthcare services such as in rural communities. Further controlled studies with greater sample size could help further expand our results.